2020
DOI: 10.1371/journal.pmed.1003356
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of children born with congenital anomalies: A systematic review and meta-analysis of population-based studies

Abstract: Background Following a reduction in global child mortality due to communicable diseases, the relative contribution of congenital anomalies to child mortality is increasing. Although infant survival of children born with congenital anomalies has improved for many anomaly types in recent decades, there is less evidence on survival beyond infancy. We aimed to systematically review, summarise, and quantify the existing population-based data on long-term survival of individuals born with specific major congenital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 87 publications
(386 reference statements)
4
64
0
2
Order By: Relevance
“…Research has shown that the survival of infants with congenital anomalies has improved in recent years (Glinianaia et al, 2020; Schneuer et al, 2019; Tennant, Pearce, Bythell, & Rankin, 2010; Wang, Hu, Druschel, & Kirby, 2011). However, other studies have found no significant change in survival (Dastgiri, Gilmour, & Stone, 2003; Roncancio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the survival of infants with congenital anomalies has improved in recent years (Glinianaia et al, 2020; Schneuer et al, 2019; Tennant, Pearce, Bythell, & Rankin, 2010; Wang, Hu, Druschel, & Kirby, 2011). However, other studies have found no significant change in survival (Dastgiri, Gilmour, & Stone, 2003; Roncancio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Another poor prognostic factor for newborns with NTDs has been addressed as concurrence of NTDs with other congenital abnormalities, chromosomal aberrations and genetic syndromes. 14,16 The major reason for this observation is that isolated cases of NTD tend to be less complicated. 16 On the other hand, it has been shown that early intervention after birth enhances the survival and well being of the neonates diagnosed with NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 The major reason for this observation is that isolated cases of NTD tend to be less complicated. 16 On the other hand, it has been shown that early intervention after birth enhances the survival and well being of the neonates diagnosed with NTDs. 14,15 The timing of surgery for postnatal treatment of NTD remains a controversial topic in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The European surveillance of congenital anomalies (EUROCAT) network of population-based CA registries provides essential epidemiologic information and surveillance on CAs in Europe but information is mainly collected up to a baby's first year of life [2][3][4]. There is little information on survival after one-year of age in Europe [5], with studies either analysing all anomalies combined [6] or concentrating on a few specific anomalies, such as spina bifida or Down syndrome [7,8]. One study investigated 20-year survival for a range of CAs in the North of England, but was unable to report survival for many rare CAs due to small numbers [9].…”
Section: Introductionmentioning
confidence: 99%